2007
DOI: 10.1080/03093640601058162
|View full text |Cite
|
Sign up to set email alerts
|

Balance control enhancement using sub-sensory stimulation and visual-auditory biofeedback strategies for amputee subjects

Abstract: Sub-sensory electrical or mechanical stimulation can enhance the sensitivity of the human somatosensory system to improve the balance control capabilities of elderly. In addition, clinical studies suggest that visual-auditory biofeedback can improve sensory compensation for the elderly. This study hypothesizes that the static balance and gait performance of single leg quiet standing and treadmill walking could be improved for providing proprioceptive neuromuscular facilitation using sub-sensory stimulation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 15 publications
(16 reference statements)
0
41
1
Order By: Relevance
“…These clinical tools are easy to administer and are an attractive option for clinicians who wish to monitor balance performance in the rehabilitation setting [16,17]. More recently, sophisticated laboratory instruments such as the force platform [18‐21], motion analysis technology [22‐24], and computerized dynamic posturography (CDP) [25,26] have been used to objectively quantify balance performance in individuals with an LLA. The detailed information obtained by objective and systematic testing from such instruments has the potential to significantly advance the understanding of individual impairments underlying the balance control system.…”
Section: Introductionmentioning
confidence: 99%
“…These clinical tools are easy to administer and are an attractive option for clinicians who wish to monitor balance performance in the rehabilitation setting [16,17]. More recently, sophisticated laboratory instruments such as the force platform [18‐21], motion analysis technology [22‐24], and computerized dynamic posturography (CDP) [25,26] have been used to objectively quantify balance performance in individuals with an LLA. The detailed information obtained by objective and systematic testing from such instruments has the potential to significantly advance the understanding of individual impairments underlying the balance control system.…”
Section: Introductionmentioning
confidence: 99%
“…Sub-threshold electrical stimulation and visual-auditory biofeedback rehabilitation strategies may be effective in compensating sensory loss and improving static balance and dynamic ambulation performance for persons with amputation [14].…”
Section: Figure 3: Represents Mean (±Sd) Of Sensory Organization Testmentioning
confidence: 99%
“…Previously, the use of tactile feedback for balance and postural control has been investigated for patients with vestibular disease where reduction of sway during locomotion [17] and postural stability improvement [18] were reported. At least one study [19] described work with above knee amputees to investigate the effect of providing IC and TO (detected using foot sensors) cues during ambulation, however, using visual and auditory feedback. The authors reported improvement in several dynamic gait performance measures.…”
Section: Resultsmentioning
confidence: 99%